(3ZjK GdCOH GdPj CSfLe aj TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3ojTai dOjoZ GdYhGdj aj HjhJge HfgdmI ef nZOjpQ GdNeQ hGdYSd s
(3BNQgG (B:s
(3hWGHb GdThb dgaj HgG OeYj aXdG Hjf NGa hHGOj s
(3HgG fXGe GdJYbjHIs
(3fSNI QGHYIs
(3bWYI efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs